Son of the Renegade - Browne, Reg, 1911-1981; Carpenter, Johnny, 1914-2003; Irving, Lori; Jack Schwarz Productions; Cinetel Films ([Los Angeles, CA] : Jack Schwarz Productions, 1953)
The story is set in the 1930's. Red River Johnny gathers his friends and returns to claim the heritage of his father who was outlawed many years ago by the sheriff of Red River. The present Sheriff Masters, son of the man Johnny's father shot, is his enemy. Besides facing a hostile sheriff, Johnny has to face the villain; a chap named Three Finger Jack who frames Red River Johnny for a series of bank holdups and stagecoach holdups, which worsens Johnny's case in clearing his family's name. And to make matters worse there is a back stabber in Johnny's group, who is giving out information about him to a member of Three Finger Jack. In the midst of this entire plot Johnny has a variety of women pursuing him, out of which he chooses only one. Eventually Johnny learns that Three-Finger plans to rob the town bank, and gathers his men and wipes out Three-Finger and his gang. --
John Carpenter, Lori Irving, Joan McKellen, Valley Keene, Jack Ingram, Verne Teters, Bill Coontz.
Narrator, Pat McGeehan; editor, Richard Connors.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015).
Keywords: Robbery -- Drama; Western films; Internet videos; Streaming video